The need for job creation through university industrial collaboration in Nigeria (2015)
The rate of graduate unemployment in Nigeria today has become very worrisome. Year after year, various institutions of higher learning in Nigeria turn out hundreds of graduates who storm the labour market in search of non-existing jobs. Those who are fortunate to get employment are often retrained by their establishments as some of them could hardly meet up the challenges of work. Many employers of labour in Nigeria often complain of graduate unemployability, stressing the need for collaboration between universities producing the graduates and the industries /establishment where they will work and earn a living. Also, some scholars subscribe to the opinion that such collaboration will increase the skills and productivity of university graduates in the work place. Hence, this paper dwells much on how universities and industrials can collaborate and create working situation that may facilitate graduate employability in the country.